PENGARUH PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA - Theresia Lestari; Budiman Tampubolon; Agus Sugiarto (Universitas Tanjungpura, 2021)
AbstractThis research intended to know how big model implement influence kooperatif type student teams' achievement division on geography learning to a student studying brazes XI SMA Country 1 Anjongan. Quantitative observational form, population in observational, it was a student's class of the XI IPS 4 As class of the experiment and class XI IPS 3 as the class of total control of 63 person. Observational method used is an experiment method with a shaped observational quaisy experiment with a design nonequivalent control is design's group. Samples taking tech utilize probability is sampling. Dat were collected using essay test numbers. Base observational result to be gotten geography studying Result student on experiment with kooperatif's learning model STAD type gotten by average value is 79 whereas student studying results on control with conventional learning method gotten by average value is 70 and available perbedaaan what does positives and significant among subject studying results geography that taught by kooperatif's learning model STAD type with conventional learning, where does point experiment is compared with assesses control class at XI IPS SMA Country 1 Anjongan by usufructs count effect size 0. 90 in the tall category.Keywords: Influence, Learned Result, STAD